1997
DOI: 10.1007/s004420050130
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic components of photoperiodic time measurement in the pitcher-plant mosquito, Wyeomyia smithii

Abstract: Photoperiodic time measurement regulating larval diapause in the pitcher-plant mosquito, Wyeomyia smithii, varies in a close relationship with latitude. The critical photoperiod mediating the maintenance and termination of diapause is positively correlated with latitude (r = 0.977) among six populations from southern (30-31° N), intermediate (40° N), and northern (46-49° N) latitudes in North America. The developmental response to unnaturally short and to unnaturally long photoperiods declines with increasing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…In Fig. 1C, the``valleys'' or short-day responses occur when T 24, 45, and 66 h, indicating a 21-h period (s 21 h) of the underlying pacemaker (Wegis et al 1997). Note also that the height (long-day response) of the response curves declines among populations from progressively more northern latitudes.…”
Section: Predictionsmentioning
confidence: 84%
See 4 more Smart Citations
“…In Fig. 1C, the``valleys'' or short-day responses occur when T 24, 45, and 66 h, indicating a 21-h period (s 21 h) of the underlying pacemaker (Wegis et al 1997). Note also that the height (long-day response) of the response curves declines among populations from progressively more northern latitudes.…”
Section: Predictionsmentioning
confidence: 84%
“…Previous results with W. smithii (Wegis et al 1997) have shown that in populations from more northern latitudes, Fig. 4 Developmental (longday) response of W. smithii to ASPPs with a 10-h main photophase and a 38-h scotophase (T=48).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations